Enhancing Current Density and Specific Capacitance of Nata de Coco, TEMPO, and MXene Composites through Boiling Time Variations - Yunus, Syukri; Umah, Kuntum Khairah; Abral, Hairul; Ogah, Ogah Anselm; Aulia, Aulia (LPPM Universitas Andalas, 2023)
This research aimed to enhance the current density and specific capacitance of electronic device materials to replace traditional metal materials. Composite materials that include Nata de Coco, TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl), and MXene achieve this improvement. Composite materials that include Nata de Coco, TEMPO, and MXene accomplish this improvement. Initial testing has shown that these materials initially demonstrated lower electrical properties, particularly in current density and specific capacitance, than conventional metals. To enhance their electrical properties, we employed a boiling method with variations in boiling time. The time intervals chosen were 30, 300, and 480 minutes. In the manufacturing process, Nata de Coco, previously oxidized by TEMPO, was boiled in an MXene solution at a temperature of 70°C. We tested the electrical properties of the resulting composite film, focusing on current density and specific capacitance. The measured current density values, corresponding to the different boiling times, were as follows: 0.000239 A/cm² for 30 minutes, 0.000307 A/cm² for 300 minutes, and 0.000320 A/cm² for 480 minutes. The specific capacitance values were 1.7005 F/g for 30 minutes, 1.9707 F/g for 300 minutes, and 2.0364 F/g for 480 minutes. The percentage increase in current density and specific capacitance values from 30 minutes to 300 minutes of boiling was 22% and 13.7%, respectively. For boiling from 300 to 480 minutes, the increase was 4.06% for current density and 3.22% for specific capacitance. These findings suggest that longer boiling times result in improved electrical properties. Subsequently, characteristic tests were performed, including XRD (X-ray diffraction) and SEM (Scanning Electron Microscope) analyses. The XRD results indicated that longer boiling times caused a rightward shift of the diffraction peak with a narrower peak width, signifying increased crystallinity. The highest X-ray intensity was observed in the composite boiled for 480 minutes, with a power of 847.23 counts per second (cps) and a two-theta angle of 21.31°. Additionally, the smallest crystal size was achieved with a 480-minute boiling time, measuring 138.2851 Å. In the SEM analysis, it was evident that longer boiling times led to a higher fraction of MXene within the composite film.